The Competence, Work Discipline, and Teacher Performance: The Mediating Role of Job Satisfaction in Schools - Rama Dani (Jurnal Economic Resource, 2026)
Teacher performance is a key factor in determining the quality of education, particularly at the Vocational High School (SMK) level, which demands an integration of pedagogical, professional, and work discipline competencies. Low teacher performance can impact the quality of learning and the achievement of educational goals. Various studies have shown that competence and work discipline are important factors influencing teacher performance, both directly and indirectly through job satisfaction. Therefore, this study aims to analyze the influence of competence and work discipline on teacher performance, with job satisfaction as a mediating variable at private vocational high schools in the Pancoran area, South Jakarta. This research employed a quantitative approach with a survey method. The study population comprised all teachers at SMK Cyber ​​Media Jakarta, SMK Wali Songo, and SMK Karya Teladan in the Pancoran area of ​​South Jakarta. Data collection used a questionnaire structured based on the indicators of each variable. The data were analyzed using path analysis to examine the direct and indirect effects between variables. The results of this study are expected to provide theoretical contributions to the development of human resource management studies in education and practical contributions for school administrators in improving teacher performance by strengthening competency, work discipline, and job satisfaction.